2014
DOI: 10.1111/cen.12627
|View full text |Cite
|
Sign up to set email alerts
|

Irisin: ‘fat’ or artefact

Abstract: SummarySoon after the discovery of the muscle-derived factor irisin, a great controversy arose in the literature regarding certain inconsistencies in the regulation of the fibronectin type III domain containing 5 protein (FNDC5/irisin) after exercise, as well as the unpredicted association of circulating irisin levels with parameters of adiposity in humans. Due to these questionable findings, doubts as to the identity of the soluble portion of FNDC5 as well as the real role of irisin and its possible therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
77
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 58 publications
5
77
1
3
Order By: Relevance
“…Supporting this interpretation, the antibody used in our study also recognizes the secreted FNDC5/irisin protein, as indicated by positive staining of fixed plasma proteins inside blood vessels (data not shown). In fact, antibodies (as ours) against the endogenous portion of FNDC5 protein have been previously shown to recognize secreted irisin, which has led to the proposal that the full-length FNDC5/irisin may be secreted [50]. Further supporting our interpretation, immunostaining has been successfully used to visualize irisin bound on the cell surface of recombinant irisin-treated 3T3-L1 adipocytes, which has suggested the existence of a yet-to-be-identified irisin receptor on the adipocyte cell membrane [51].…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this interpretation, the antibody used in our study also recognizes the secreted FNDC5/irisin protein, as indicated by positive staining of fixed plasma proteins inside blood vessels (data not shown). In fact, antibodies (as ours) against the endogenous portion of FNDC5 protein have been previously shown to recognize secreted irisin, which has led to the proposal that the full-length FNDC5/irisin may be secreted [50]. Further supporting our interpretation, immunostaining has been successfully used to visualize irisin bound on the cell surface of recombinant irisin-treated 3T3-L1 adipocytes, which has suggested the existence of a yet-to-be-identified irisin receptor on the adipocyte cell membrane [51].…”
Section: Discussionmentioning
confidence: 99%
“…In the human data, a decrease in serum irisin concentration at the end of an 8-week energy restriction program (70% of the daily energy requirements) positively correlated with the decreased concentration of total cholesterol, apolipoprotein B and the total cholesterol/high-density lipoprotein cholesterol ratio in patients with metabolic syndrome [23]. Crujeirais et al postulated that irisin acts as an adaptive response to counteract disturbances in glucose and lipid homoeostasis in obesity [24]. Based on previously reported human data, we can hypothesize that elevated serum irisin at baseline and after insulin infusion may represent a compensatory mechanism to maintain proper energy balance in the insulin resistant state observed in PCOS women.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous aspects of irisin biology thus remain highly controversial, as recently reviewed in [9]. Some of the controversies include the following: (1) Although at first suggested to be a myokine, more recent studies question its production by muscle and instead suggest it might primarily be an adipokine [2,26].…”
Section: Introductionmentioning
confidence: 99%
“…(3) Studies on the impact of physical activity are contradictory, some showing irisin is increased after a physical effort [5,7,15,32], others not [16,29,32]. (4) The impact of obesity and/or diabetes is contradictory [8,15,21,31], although recent work tends to support a positive association with circulating irisin levels [9]. A possible explanation for some of the contradictory results between published reports could reside in which cleavage product of FNDC5 is actually released and detected using the various kits available for its measurement [12,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%